Female Poverty in Rural Türkiye: A Case Study of Ayvacık District - Yazıcı, M.; Alkan, Hatice Isil (Springer Nature, 2025)
Türkiye is a country that has struggled with poverty since the past. The high level of gender inequality in the country causes women to experience poverty more severely. Poverty is notable in rural regions and rural women are the poorest of the poor. Although female poverty is a prominent problem in the country, few studies address this issue and studies investigating women’s poverty in rural areas are scarce. This study, which is vital in terms of development, tries to reveal the determinants of women’s poverty in rural Türkiye, in the specific case of Ayvacık district of Samsun province, and aims to develop policy recommendations to alleviate poverty. In this context, 80 women were included in the research using the mixed method and snowball sampling technique. The quantitative data obtained from the research were analysed using descriptive statistics, while the qualitative data were analysed using the MAXQDA 2024 Data Analysis Software. According to the thematic analysis conducted within the qualitative analysis framework, five main themes and 31 hierarchical codes are created. The findings of the study indicate that patriarchal ideology, the high share of agriculture in the economy, the unpaid nature of women’s labour in agriculture, women’s lack of property ownership, low levels of awareness and low levels of education directly affect female poverty. The quantitative analysis reveals that the women in the research area are strikingly poor. It has been determined that agriculture accounts for a higher proportion of the economy in villages far from the district center and female poverty is more severe in these villages. The findings also highlight that agriculture must cease to be the sole employment-generating sector in rural regions. Considering that the patriarchal structure devalues women’s labour, it becomes clear that development policies that take gender equality into account in the region are a much more effective solution. © The Author(s), under exclusive licence to Springer Nature Switzerland AG 2025.
Keywords: Agriculture; Patriarchy; Poverty; Rural Women; Türkiye